2008
DOI: 10.1097/hjh.0b013e3282f2b90c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the C825T polymorphism of the GNB3 gene on body adiposity and blood pressure in fertile and menopausal women: a population-based study

Abstract: An interaction exists between the C825T polymorphism and menopause in controlling body adiposity and blood pressure in women. Adiposity and SBP are higher in menopausal than in fertile women, provided they have the CC genotype. TT fertile women show the same adiposity as those in menopause. Men have the same excess adiposity as menopausal women, independent of the GNB3 genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
1
22
0
1
Order By: Relevance
“…The SNP C825T of the GNβ3 gene has been reported to be associated with elevated metabolic indexes in different groups of patients suffering from hypertension, diabetes or cardiovascular disease (Brand et al, 2003;Casiglia et al, 2008;Danoviz et al, 2006;Hayakawa et al, 2007;Kopf et al, 2008;Meirhaeghe et al, 2005). Moreover, the variant has also been found to be associated with medication-induced metabolic disturbances (Hauner et al, 2003;Peters et al, 2008;Souza et al, 2008;Wang et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…The SNP C825T of the GNβ3 gene has been reported to be associated with elevated metabolic indexes in different groups of patients suffering from hypertension, diabetes or cardiovascular disease (Brand et al, 2003;Casiglia et al, 2008;Danoviz et al, 2006;Hayakawa et al, 2007;Kopf et al, 2008;Meirhaeghe et al, 2005). Moreover, the variant has also been found to be associated with medication-induced metabolic disturbances (Hauner et al, 2003;Peters et al, 2008;Souza et al, 2008;Wang et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…[8][9][10][11][12] A group of 1438 subjects matched with cases for age (Ϯ 3 years) and sex, who had no history of cancer and had not experienced either venous (including SVT) or arterial thromboembolic disorders before the beginning of the observation, served as study controls. For 36 cases, only 1 matched control could be identified.…”
Section: Controlsmentioning
confidence: 99%
“…The mechanism whereby the 825T variant may lead to hypertension remains unknown, but it may involve an increase of Na-H exchanger activity (Siffert, 1996) which enhanced renal sodium reabsorption and induced the BP increase. Several studies have demonstrated that the 825T allele of GNB3 is associated with hypertension (Benjafiel et al, 1998, Beige et al, 1999, Dong et al, 1999, Hengstenberg et al, 2001, Timberlake et al, 2001, Casiglia et al, 2008. Together, these studies highlight the importance of the GBN3/C825T variant gene in EH.…”
Section: G Proteinsmentioning
confidence: 72%
“…A polymorphism C3T at nucleotide 825 in exon 10 of the 3 subunit of GTP binding protein (GNB3/C825T) has been identified (Bohm et al, 1997). This polymorphism is associated with enhanced intracellular signal transduction and has been reported to be associated with a variety of cardiovascular risk factors, including hypertension , Schunkert et al, 1998, Benjafield et al, 1998, obesity , Casiglia et al, 2008, diabetes (Bluthner et al, 1999) or dyslipidemia (Ishikawa et al, 2000, Hayakawa et al, 2007. A significantly higher frequency of the T allele has been identified in EH (Beige et al, 1999, Siffert, 1996.…”
Section: G Proteinsmentioning
confidence: 99%